An ozone episode over the Pearl River Delta in October 2008. (December 2015) - Shen, Jin; Zhang, Yuanhang; Wang, Xuesong; Li, Jinfeng; Chen, Hao; Liu, Run; Zhong, Liuju; Jiang, Ming; Yue, Dingli; Chen, Duohong; Lv, Wei
Abstract: The north and east Pearl River Delta (PRD) is usually a clean, upwind area in autumn. Serious ozone pollution there in mid-late October 2008 was first discovered and then analyzed. Trajectory analysis, process analysis, ozone source apportionment technology, and sensitivity analysis were used to study this episode. Under the influence of a weak south wind, the precursors emitted in Guangzhou and Foshan were transported to the north and northeast PRD and formed ozone there, which resulted in high ozone concentration (>100 ppb). As the wind direction later transited to northerly, the precursors in the northeast PRD that originated from the central and west PRD were transported to the south, and caused severe ozone pollution in the southeast PRD. The ozone contributed by chemical processes reached >20 ppb/h in Jinguowan. More than 40 ppb ozone was contributed by the precursor emission in the central and west PRD during the episode. The ozone concentration was highly sensitive to the precursor emission in the PRD region in the high-ozone situations. This episode showed the complexity of regional pollution in the PRD. When the PRD is controlled by a low air pressure system and then cold air moves from northern China to the south, the risk of ozone pollution in the north and southeast PRD increases. Highlights: The IPR, OSAT, GOAT, and HDDM were used to investigate an ozone episode in the PRD. Guangzhou and Foshan sources had a great impact on the downwind area. High ozone zone changed markedly as the wind direction changed in the PRD. When the wind changed from S to N, ozone pollution occurred in the southeast PRD.